2020
DOI: 10.1080/20008198.2020.1780832
|View full text |Cite
|
Sign up to set email alerts
|

Stressors, coping and symptoms of adjustment disorder in the course of the COVID-19 pandemic – study protocol of the European Society for Traumatic Stress Studies (ESTSS) pan-European study

Abstract: Background: During the current COVID-19 pandemic, the people in Europe are exposed to self-isolation, quarantine, job loss, risk of contracting COVID-19, or grief of loved ones. Such a complex array of stressors may lead to symptoms of adjustment disorder or posttraumatic stress disorder. This research protocol describes a study launched by the European Society of Traumatic Stress Studies (ESTSS) to investigate the impact of the COVID-19 pandemic on symptoms of adjustment disorder across European countries. Ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 36 publications
(35 reference statements)
1
69
0
9
Order By: Relevance
“…Female GPs showed a lower adaptation level to the pandemic than male GPs, which can be translated into a faulty immune status compared to males due to the higher prevalence of chronic diseases, but also to a lower stress management level compared to men [ 31 ]. There are significant differences between female and male subjects, regarding the adjustment to pandemic, defined according to the literature data [ 32 , 33 ] as the management of the crisis and the level of adaptation to the new working conditions. The female subjects considered that their adaptation capacities to the new conditions imposed by the pandemic were significantly more solicited, ( t (675) = 2.167, p < 0.031).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female GPs showed a lower adaptation level to the pandemic than male GPs, which can be translated into a faulty immune status compared to males due to the higher prevalence of chronic diseases, but also to a lower stress management level compared to men [ 31 ]. There are significant differences between female and male subjects, regarding the adjustment to pandemic, defined according to the literature data [ 32 , 33 ] as the management of the crisis and the level of adaptation to the new working conditions. The female subjects considered that their adaptation capacities to the new conditions imposed by the pandemic were significantly more solicited, ( t (675) = 2.167, p < 0.031).…”
Section: Resultsmentioning
confidence: 99%
“…According to the European Society of Traumatic Stress, the latest pandemic showed that during and after the pandemic, one in four Europeans were affected by post-traumatic stress [ 33 ]. Six months after the first global lockdown, it became obvious that 2020 made its debut with the most virulent pandemic, when the entire world was unplugged.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these may include being in quarantine, unemployment, financial difficulties and stigma, that can lead to adaptation difficulties in many suffering from the disease. Unsurprisingly, this complex array of stressors can lead to psychiatric problems such as adjustment disorder, depression, and anxiety ( Kazlauskas and Quero, 2020 ; Lotzin et al, 2020 ; Mazza et al, 2020 ; Xie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The original, four‐item PC‐PTSD screener was noted as one of the best‐performing screeners in a systemic review of 15 PTSD screening instruments and has been used in diverse populations 30,31 . Because of its brevity and ease in administration, the revised PC‐PTSD‐5 was used in our investigation and has been used by others during the COVID‐19 pandemic 32‐34 . In a recently published study conducted on the general public from 20 countries 16.4% of women and 17.7% of men screened positive on the PC‐PTSD‐5 32 .…”
Section: Limitationsmentioning
confidence: 99%
“…In a recently published study conducted on the general public from 20 countries 16.4% of women and 17.7% of men screened positive on the PC‐PTSD‐5 32 . Currently, a cohort study of stressors, coping, and symptoms of adjustment disorder in the course of the COVID‐19 pandemic is being undertaken in 10 European countries utilizing the PC‐PTSD‐5 34 . We anticipate that these findings will contribute to ours in the assessment of stressors during the COVID‐19 pandemic.…”
Section: Limitationsmentioning
confidence: 99%